CTNI-14. A 3-ARM, PHASE IIA TRIAL OF SAFETY & EFFICACY OF OLINVACIMAB, A MONOCLONAL ANTIBODY TO VEGFR2 IN PATIENTS WITH RECURRENT GLIOBLASTOMA MULTIFORME WITH IMAGING AND PK/PD ASSESSMENTS: FINAL REPORT. (9th November 2020) - Cher, Lawrence; Nowak, Anna; Iatropoulos, George; Bowyer, Samantha; Gan, Hui; Long, Anne Poh; Bynevelt, Michael; Jackson, Graeme; Lee, Seon Young; Lee, Weon Sup; Yoo, Jin-San
Abstract: The VEGF pathway remains an important target in GBM given its vascularity and autocrine VEGF signalling. Olinvacimab (TTAC-0001) is a fully humanised VEGFR2 Mab that binds and inhibits the receptor. This report assesses the safety, dosing schedules and efficacy of Olinvacimab in recurrent GBM. We conducted a two-site, 3 arm, open-label study of Olinvacimab in recurrent GBM. Eligible patients were ≥18 years with RANO-measurable lesion, KPS ≥ 80, and had completed chemoradiotherapy without prior bevacizumab therapy. We assessed three arms, 8 mg/kg and 12mg/kg weekly for 3 of every 4 weeks, and 12 mg/kg weekly. Three patients were treated in arms 1 and 2 and 6 in arm 3. Safety assessments were performed prior to dose escalation. The main toxicity was development of grade 1 (67%) and 2 (8%%) cutaneous haemangiomas. Common toxicities seen with other VEGF directed therapies, including hypertension, impaired wound healing, and proteinuria were not seen in this cohort. Efficacy was assessed by MRI using RANO criteria. 6 month PFS was 17%, with disease control in 25%, with steroid dose reduction. The longest response was 15 months. On DCE MRI, there was no significant difference in perfusion parameters between baseline and 1st follow-up MRI comparing those with SD and PD. However, 6 of 12 patients showed decreased Ktrans > 20 % of baseline, consistent with an anti-angiogenic effect of Olinvacimab. Pharmacokinetics showed a decreased clearance rate and increased half-life of Olinvacimab compared to the prior Phase I study. Pharmacodynamic studies showed significantly higher levels of angiogenic markers, particularly VEGF-A in those treated at 12mg/kg vs arm 1. VEGF-A, C and D levels were elevated in patients with SD compared to those with PD. Conclusion: Olinvacimab was well tolerated with a different toxicity profile to other VEGFR directed therapies. There were promising responses in 25% of patients.